UMAT ISLAM INDONESIA (BUKAN) TERORIS: MENAMPIK ISU TERORISME DENGAN PENDIDIKAN KEWARGANEGARAAN - Lilis Sarifatul Ajariyah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2017)
The issue of Islam as a terrorist blows louder. State of Indonesia as the country with the most Islamic religion being similarly affected, especially because many Muslim citizens suspected and already proven to be involved in the case terosisme deadly juwa. To dismiss these issues, civic education is needed to instill nationalism that every citizen is not easily commit acts of terrorism, by reason of the difference, and so on. Citizenship education also provide a gap to every person to be able to live freely and comfortably in the country. Therefore, the implementation of civic education should be emphasized at all levels of formal and non-formal education because Islam alone is not enough.